Pengaruh Kompetensi dan Kompensasi Terhadap Kinerja Karyawan di PLN ULP Rajapolah - Mochamad Faisal Andiyani (PT Maju Malaqbi Makkarana, 2023)
The purpose of this study was to determine the effect of competence on employee performance in PLN ULP Rajapolah employees, to determine the effect of compensation on employee performance in PLN ULP Rajapolah employees and to determine the effect of competence and compensation on employee performance in PLN ULP Rajapolah employees. The samples in this study are PLN ULP Rajapolah employees, totaling 51 people. This research was conducted by collecting data using a questionnaire data collection technique, then testing the data with multiple linear regression analysis. The results of this study indicate that (1) there is an influence of competence on employee performance at PLN ULP Rajapolah Employees. (2) There is an effect of compensation on employee performance at PLN ULP Rajapolah Employees. (3) There is an influence of competence and compensation on employee performance at PLN ULP Rajapolah Employees.